2020
DOI: 10.3897/folmed.62.e49926
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Mucosal Melanoma: a Complete Remission after Immunotherapy and '0-7-21' Radiotherapy Regimen (24 Gy/3 fractions/21 days)

Abstract: We present the case of a patient with vaginal mucosal melanoma who underwent complete remission after immunotherapy and ‘0-7-21’ radiotherapy regimen (24 Gy/3 fractions/21 days). An 80-year-old woman had a biopsy of a voluminous vaginal lesion and received a histological diagnosis of melanoma with angiomatoid aspects. The patient underwent immunotherapy with pembrolizumab 2 mg/kg every 3 weeks and was sent to our attention for planning radiotherapy as the extent of the lesion did not make i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…While long-term survival remains low, local control of 74% at 2 years was achieved with postoperative or definitive RT, which is in line with prior studies. 2 , 18 , 20 , 21 Case reports of RT and ICI for vaginal 22 , 23 , 24 , 25 and anorectal 26 , 27 melanoma have also demonstrated durable responses. We found that favorable local control was possible even in patients with node-positive disease, with 2-year overall survival 100% and local control 100%.…”
Section: Discussionmentioning
confidence: 99%
“…While long-term survival remains low, local control of 74% at 2 years was achieved with postoperative or definitive RT, which is in line with prior studies. 2 , 18 , 20 , 21 Case reports of RT and ICI for vaginal 22 , 23 , 24 , 25 and anorectal 26 , 27 melanoma have also demonstrated durable responses. We found that favorable local control was possible even in patients with node-positive disease, with 2-year overall survival 100% and local control 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Pembrolizumab also showed efficacy in a patient with vulva verrucous carcinoma in neoadjuvant setting in association with chemotherapy [14]. Pembrolizumab also demonstrated good disease control in rare histologies, such as metastatic vaginal adenocarcinoma, clear cell carcinoma of the vulva, and vulvo-vaginal mucosal melanoma [15‒18].…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports concerning this combination therapy for vaginal melanoma. Parisi et al (31) reported that a patient with vaginal melanoma achieved CR after HFRT combined with ICIs. Schonewolf et al (32) presented two cases of vaginal melanoma, where both patients achieved CR.…”
Section: Discussionmentioning
confidence: 99%